Where are the links? Using a causal loop diagram to assess interactions in healthcare coordination for youth experiencing homelessness in Toronto, Canada - Hudani, Alzahra; Long, Janet; Labonté, Ronald; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Youth experiencing homelessness (YEH) suffer from poorer physical and mental health outcomes than stably housed youth. Additionally, YEH are forced to navigate fragmented health and social service systems on their own, where they often get lost between systems when transitioning or post-discharge. Inevitably, YEH require support with health system navigation and healthcare coordination. The aim of this study is to understand interactions within and between the emergency youth shelter (EYS) and health systems that affect healthcare coordination for YEH in Toronto, Canada, and how these interactions can be targeted to improve healthcare coordination for YEH. Methods This study is part of a larger qualitative case study informed by the framework for transformative systems change. To understand interactions in healthcare coordination for YEH within and between the EYS and health systems, we developed a causal loop diagram (CLD) using in-depth interview data from 24 key informants at various levels of both systems. Open and focused codes developed during analysis using Charmaz’s constructivist grounded theory methodology were re-analysed to identify key variables, and links between them to create the CLD. The CLD was then validated by six stakeholders through a stakeholder forum. Results The CLD illustrates six balancing and one reinforcing feedback loop in current healthcare coordination efforts within the EYS and health systems, respectively. Increasing EYS funding, building human resource capacity, strengthening inter and intra-systemic communication channels, and establishing strategic partnerships and formal referral pathways were identified among several other variables to be targeted to spiral positive change in healthcare coordination for YEH both within and between the EYS and health systems. Conclusions The CLD provides a conceptual overview of the independent and integrated systems through which decision-makers can prioritize and guide interventions to strengthen healthcare coordination within and between the EYS and health systems. Overall, our research findings suggest that key variables such as streamlining communication and improving staff–youth relationships be prioritized, as each of these acts interdependently and influences YEH’s access, quality and coordination of healthcare.